Determination of Morphological, Agricultural and Cytological Characters of Some Lathyrus species - ACAR, ZEKI; BASARAN, UGUR (Asian Journal of Chemistry, 2010)
In this study, some morphological, agricultural and cytological characters of naturally grown Lathyrus species (Lathyrus hirsutus L, L. ochrus L. (DC), L. aphaca L. var affinis, L. laxiflorus ssp laxiflorus, L. annuus L., L. sphaericus Retz.) were investigated in 2003 and 2004. Average plant height varied between 32.50 and 131.00 cm, dry yield/plant between 0.32 and 22.16 g/plant, crude protein of hay between 15.00 and 21.00 % and, 20.51 and 28.36 % in seed and ash content between 7.06 and 10.82 %. K, Ca, Mg, Fe, Zn and Mn contents were determined in both whole plants and seeds. Chromosomal and cytogenetic studies have shown that investigated Lathyrus species has diploid with 2n = 14 somatic chromosome number.